Changes in microstructure characteristics of cement paste on carbonation. (July 2018) - Shah, Vineet; Scrivener, Karen; Bhattacharjee, Bishwajit; Bishnoi, Shashank
Abstract: This study investigates the influence of carbonation on the microstructure of cement paste cast with Ordinary Portland Cement (OPC), fly ash based Portland Pozzolana Cement (PPC) and Limestone Calcined Clay Cement (LC 3 ) using X-ray diffraction (XRD), thermal analysis (TGA), scanning electron microscope (SEM) and mercury intrusion porosimeter (MIP). A comparison is made between samples exposed to 3% carbon dioxide concentration and those exposed to natural CO2 concentrations. It is observed that the products formed on carbonation are similar in both the exposure conditions. Distinct rims corresponding to decalcified C-S-H are observed around clinker grains in the carbonated samples. Coarsening of pore structure is observed on carbonation in all the cements and an increase in the total porosity is observed in blended cements. Thermodynamic modeling indicates irrespective of the type of cement the total solid volume is reduced on complete carbonation. The volume change occurring on carbonation obtained from experimental results and thermodynamic modeling are compared.